Evaluation of Numerical Analysis for Earthquake Resistance of Retaining Wall Using Gabions - Tsuyoshi Nishi; Tadashi Hara; Hiroshi Nakazawa; Daisuke Suetsugu (EPI International Journal of Engineering, 2019)
In developing countries, gabions are widely used in several construction works, like road, river, countermeasures against slope failure and so on, because of their easy operation and low cost. In 2015 Nepal Gorkha Earthquake, a lot of retaining walls using gabions were not damaged against the strong earthquake because of their high flexibility. However, some deformation or declination were reported dpending on retaining wall types and ground conditions behind retaining walls. Therefore, in order to evaluate the earthquake resistance and residual deformations of retaining walls using gabions widely observed in Nepal, full-scale shake table tests and laboratory tests were conducted in previous studies. In this study, elemental simulations for determination of the analysis parameters based on the results of triaxial compression tests were carried out to check the validity of parameters. Then, a series of numerical analysis using proposed model was performed to reproduce the dynamic behaviors of full-scale shake table tests and evaluate the earthquake resistance of retaining wall using gabions. According to the results of these numerical analysis, it was confirmed that proposal model adequately could simulate the dynamic response of retaining walls in the full-scale shake table tests. and it was also cleared that the stepwise type retaining wall was superior to that of vertical type from the standpoint of earthquake stability against sliding and overturning.